Analysis of Financial Performance on Profitability with Non Performace Financing As Variable Moderation - Yusuf, Muhammad; Surjaatmadja, Surachman (International Journal of Economics and Financial Issues, 2018)
Profitability is the ability of banks in generating profits effectively and efficiently The purpose of this study is to determine the effect of CAR and FDR on profitability (proxies with Return On Assets) with NPF as a moderation variable. The population of this study is sharia commercial banks in Indonesia period 2012-2016 which amounted to 12 banks. This study uses purposive sampling method for sampling, the selection of samples with certain criteria, so that this research samples obtained as many as 11 banks. The data used in this research is secondary data. Data analysis used is multiple linear regression analysis. Meanwhile, to test the effect of the moderating variable on the influence between independent variable and dependent variable using moderated regression analysis (MRA). The results showed that partially, CAR and FDR have a significant positive effect on profitability and BOPO have a significant negative effect on profitability. While the NPF has no significant effect on the relationship between CAR with profitability and the relationship between FDR with profitability, while the NPF has a significant negative effect on the relationship between BOPO with profitability. However, NPF as a moderating variable has an insignificant influence (unable to moderate) the CAR relationship to ROA and NPF as moderating variable has an insignificant influence (unable to moderate) FDR relation to ROA and NPF as moderating variable has significant negative effect (able to moderate) BOPO relationship to ROA sharia public bank in Indonesia period 2012-2016 Keywords: Sharia Commercial Bank, CAR, BOPO, FDR, NPF, Profitability JEL Classifications: M21, O61